Gene analysis techniques and susceptibility gene discovery in non-BRCA1/BRCA2 familial breast cancer. (June 2015) - Aloraifi, Fatima; Boland, Michael R.; Green, Andrew J.; Geraghty, James G.
Abstract Breast cancer is the leading cause of cancer deaths in females worldwide occurring in both hereditary and sporadic forms. Women with inherited pathogenic mutations in the BRCA1 or BRCA2 genes have up to an 85% risk of developing breast cancer in their lifetimes. These patients are candidates for risk-reduction measures such as intensive radiological screening, prophylactic surgery or chemoprevention. However, only about 20% of familial breast cancer cases are attributed to mutations in BRCA1 and BRCA2, while a further 5–10% are attributed to mutations in other rare susceptibility genes such as TP53, STK11, PTEN, ATM and CHEK2. A multitude of genome wide association studies (GWAS) have been conducted confirming low-risk common variants associated with breast cancer in excess of 90 loci, which may contribute to a further 23% of the heritability. We currently find ourselves in "the next generation", with technologies offering deep sequencing at a fraction of the cost. Starting off primarily in a research setting, multi-gene panel testing is now utilized in the clinic to sequence multiple predisposing genes simultaneously (otherwise known as multi-gene panel testing). In this review, we focus on the hereditary breast cancer discoveries, techniques and the challenges we face in this complex disease, especially in the light of the vast amount of data we now have at hand. It has been 20 years since the first breast cancer susceptibility gene has been discovered and there has been substantial progress in unraveling the genetic component of the disease. However, hereditary breast cancer remains a challenging topic subject to common debate.